2014
DOI: 10.1038/ncomms4064
|View full text |Cite
|
Sign up to set email alerts
|

MED18 interaction with distinct transcription factors regulates multiple plant functions

Abstract: Mediator is an evolutionarily conserved transcriptional regulatory complex. Mechanisms of Mediator function are poorly understood. Here we show that Arabidopsis MED18 is a multifunctional protein regulating plant immunity, flowering time and responses to hormones through interactions with distinct transcription factors. MED18 interacts with YIN YANG1 to suppress disease susceptibility genes glutaredoxins GRX480, GRXS13 and thioredoxin TRX-h5. Consequently, yy1 and med18 mutants exhibit deregulated expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
169
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(173 citation statements)
references
References 51 publications
3
169
1
Order By: Relevance
“…1). Although med8, med13, and med18 have been shown to be more susceptible than the wild type to the necrotrophic fungal pathogens B. cinerea and A. brassicicola (Kidd et al, 2009;Lai et al, 2014;Zhu et al, 2014), they did not show enhanced susceptibility to S. sclerotiorum. This is probably because MED8, MED13, and MED18 do not play a major role in regulating S. sclerotiorum-induced transcriptome changes (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…1). Although med8, med13, and med18 have been shown to be more susceptible than the wild type to the necrotrophic fungal pathogens B. cinerea and A. brassicicola (Kidd et al, 2009;Lai et al, 2014;Zhu et al, 2014), they did not show enhanced susceptibility to S. sclerotiorum. This is probably because MED8, MED13, and MED18 do not play a major role in regulating S. sclerotiorum-induced transcriptome changes (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…MED14, MED15, MED16, and MED19a have been shown to regulate the SA-triggered immunity against biotrophic and hemibiotrophic pathogens (Canet et al, 2012;Zhang et al, 2012Zhang et al, , 2013Caillaud et al, 2013), whereas MED8, MED12, MED13, MED16, MED21, MED25, and CDK8 have been found to function in JA/ET-mediated immunity against necrotrophic pathogens (Dhawan et al, 2009;Kidd et al, 2009;Zhang et al, 2012;Zhu et al, 2014). MED18 also functions in resistance to necrotrophic pathogens, but the resistance is independent of the JA/ET signaling (Lai et al, 2014). Interestingly, the Arabidopsis oomycete pathogen Hyaloperonospora arabidopsidis RXLR effector44 (HaRxL44) interacts with MED19a and promotes its degradation, which shifts the balance of defense transcription from SA to JA/ET signaling (Caillaud et al, 2013).…”
mentioning
confidence: 99%
“…MED8, MED12, MED13, MED14, MED16, MED21, MED25 and CDK8 have been found to function in JA/ET-mediated immunity against necrotrophic pathogens (Dhawan et al 2009; Zhang et al 2012). MED18 also operates in resistance to necrotrophic pathogens, but the resistance appears to be independent of the JA/ET signalling (Lai et al 2014). Wang et al (2016) showed that MED33A/B contributed to the necrotrophic fungal pathogen Botrytis cinerea induced expression of the PDF1.2 defensin, HEVEIN-LIKE and BASIC CHITINASE defence genes and is required for full-scale basal resistance to B. cinerea , which demonstrated a decisive role for MED33 against necrotrophic fungal pathogens.…”
Section: Resistance and Signalling In Plantsmentioning
confidence: 99%
“…Chromatin associated with GFP-MOS1 was precipitated with anti-GFP antibodies and four FLC genomic sites ( Fig. 4d), including the SUF4-binding site 23 of the FLC promoter, were analysed for their abundance in the precipitated chromatins by quantitative (q)-PCR. Compared with the no antibody (Ab) IP sample, the Ab IP sample had a five-fold enrichment at the SUF4-binding site, while no significant enrichment was found at three other sites: TATA box, a coding fragment and the terminator (Fig.…”
Section: Loss Of Mos1 Function Suppresses An Autoimmune Phenotypementioning
confidence: 99%